Amazon's distribution space: Constructing a 'labour fix' through digital Taylorism and corporate Keynesianism - Mostafa Henaway (ZFW - Advances in Economic Geography, 2023)
Amazon is one of the largest e-commerce corporations in the world and has built a reputation for fast, low-cost service. To rapidly and efficiently move goods from production to consumption, however, Amazon relies on a logistics network that entails significant investments in infrastructure (physical and human) and these investments present a challenge for capital accumulation. In this paper, I examine the labour practices that Amazon employs within its distribution work spaces to address this challenge. The analysis is based on a case study of Amazon's distribution facilities (fulfilment centres and delivery stations) in Montreal, Quebec. It draws on ethnographic research as a community organizer and semi-structured interviews with workers (present and former), trade union representatives and public policy experts to identify Amazon's key strategies. Building on past studies on the platform economy, I illustrate how Amazon relies on 'digital Taylorism' (Staab & Nachtwey, 2016), involving the use of digital technologies to structure and control the labour process and surveil workers, as a key strategy. However, I further illustrate how Amazon seeks to balance the harmful effects of digital Taylorism with what I term 'corporate keynesianism' (i.e., social welfare benefits) to attain a 'labour fix', i.e., the steady supply of precarious, compliant labour needed to sustain the logistics machine.
Keywords: 330; Amazon; digital Taylorism; e-commerce; labour process; logistics; Montreal